Reduction in smoke emitted and fire hazard presented by flexible poly (vinyl chloride) through novel synthesis of SnO2 supported by activated carbon spheres. (21st June 2018) - He, Shaorui; Wu, Weihong; Zhang, Mengjiao; Han, Hongda; Jiao, Yunhong; Qu, Hongqiang; Xu, Jianzhong
Abstract : A novel catalyst consisting of SnO2 supported by activated carbon spheres (ACS), referred to as "ACS@SnO2, " was demonstrated as being much more efficient than either ACS or SnO2 alone. As such, it is capable of improving the thermal stability and flame retardancy of flexible poly (vinyl chloride) (fPVC). The resulting ACS@SnO2 composite exhibits a higher reactivity and excellent stability due to the presence of evenly dispersed SnO2 particles attached to the ACS, as well as the high degree of graphitization of the ACS. Smoke suppression and the synergistic flame‐retardant effect of the ACS@SnO2 on the fPVC were thoroughly investigated by performing a cone calorimeter test and thermogravimetric analysis. The cone calorimeter test data reveal that the addition of the ACS@SnO2 greatly improved the flame retardancy of the fPVC, with 32% and 58.4% decreases in the peak heat release rate and smoke production rate, respectively. This is attributed to the formation of a continuous and compact protective layer and the synergistic effects of the ACS and SnO2 in promoting the ability of the fPVC to isolate heat and oxygen. Furthermore, the ACS@SnO2 /fPVC composite produced greatly increased amounts of char residue, thereby attenuating the fire hazard presented by fPVC composites.